Motivations for Work Out-Migration among Rural Households: A Case of Rural Tarai, Nepal - Gurung, Yogendra B; Khatiwada, Padma Prasad (Nepal Population Journal, 2026)
A nation whose economy is based primarily on agriculture is becoming increasingly concerned about the tendency of rural out-migration. The focus of this research is on important motivating factors that drive migration from rural areas. The stories of the rural residents of Eastern Tarai village serve as the basis for this interpretation. Although De Jong and Fawcett's value-expectancy model is helpful in explaining rural out-migration, this work has not fully adhered to it. To comprehend the results, two motivational concepts that are closely related to "demotivation's" and "expectations" have been conceptualized. Demotivation, which are based on four prevailing situations land poverty and unemployment, deteriorating agriculture, an inadequate educational system, and ongoing social unrest are the negative motivation of rural people with relation to their current agricultural livelihood. Future social standing, lifestyle choices, and economic prosperity are all anticipated. When people decide to migrate, they do so with the hope of future affluence and social advancement. Migration has thereby contributed to the rural population's transition from reliance on agriculture to remittance dependency.